Association of oxidative stress and inflammatory metabolites with Alzheimer’s disease cerebrospinal fluid biomarkers in mild cognitive impairment - Ahmad, Shahzad; Yang, Wei; Orellana, Adelina; Frölich, Lutz; de Rojas, Itziar; Cano, Amanda; Boada, Mercè; Hernández, Isabel; Hausner, Lucrezia; Harms, Amy C.; Bakker, Margot H. M.; Cabrera-Socorro, Alfredo; et al. (Alzheimer's research & therapy, 2024)
Isoprostanes and prostaglandins are biomarkers for oxidative stress and inflammation. Their role in Alzheimer's disease (AD) pathophysiology is yet unknown. In the current study, we aim to identify the association of isoprostanes and prostaglandins with the Amyloid, Tau, Neurodegeneration (ATN) biomarkers (Aβ-42, p-tau, and t-tau) of AD pathophysiology in mild cognitive impairment (MCI) subjects. Targeted metabolomics profiling was performed using liquid chromatography-mass spectrometry (LCMS) in 147 paired plasma-CSF samples from the Ace Alzheimer Center Barcelona and 58 CSF samples of MCI patients from the Mannheim/Heidelberg cohort. Linear regression was used to evaluate the association of metabolites with CSF levels of ATN biomarkers in the overall sample and stratified by Aβ-42 pathology and APOE genotype. We further evaluated the role of metabolites in MCI to AD dementia progression. Increased CSF levels of PGF2α, 8,12-iso-iPF2α VI, and 5-iPF2α VI were significantly associated (False discovery rate (FDR) < 0.05) with higher p-tau levels. Additionally, 8,12-iso-iPF2α VI was associated with increased total tau levels in CSF. In MCI due to AD, PGF2α was associated with both p-tau and total tau, whereases 8,12-iso-iPF2α VI was specifically associated with p-tau levels. In APOE stratified analysis, association of PGF2α with p-tau and t-tau was observed in only APOE ε4 carriers while 5-iPF2α VI showed association with both p-tau and t-tau in APOE ε33 carriers. CSF levels of 8,12- iso-iPF2α VI showed association with p-tau and t-tau in APOE ε33/APOE ε4 carriers and with t-tau in APOE ε3 carriers. None of the metabolites showed evidence of association with MCI to AD progression. Oxidative stress (8,12-iso-iPF2α VI) and inflammatory (PGF2α) biomarkers are correlated with biomarkers of AD pathology during the prodromal stage of AD and relation of PGF2α with tau pathology markers may be influenced by APOE genotype.